Use of a theoretical prediction method and quantum chemical calculations for the design, synthesis and experimental evaluation of three green corrosion inhibitors for mild steel - Machado Fernandes, Caio (2020)
Three phenylmethanimine derivatives (Schiff bases) were designed after a theoretical prediction of their corrosion inhibition efficiencies and a corroboration through the use of quantum chemical calculations. The molecules were then prepared using a classical condensation reaction between aldehydes and amines but taking in account the tenets of green chemistry. Their application as corrosion inhibitors for ASTM A36 steel in 1 mol L−1 hydrochloric acid media was explored by means of a weight loss analysis, electrochemical tests and a surface morphology analysis to physically evaluate the metallic sacrifice surfaces used. The results of the electrochemical tests revealed that the three compounds have a good anti-corrosion capacity and act as mixed-type corrosion inhibitors. In addition, cross-checking the data from weight loss analysis and electrochemical tests confirm Langmuir monolayer formation theory. The corrosion inhibition efficiencies found range between 83.5 and 95.6%.